IRONY AS A TOOL OF SOCIAL CRITICISM IN CHARLES DICKENS' GREAT EXPECTATIONS (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
​   This thesis examines the multifaceted role of irony as a strategic instrument of social criticism in Charles Dickens’s masterpiece, Great Expectations. By analyzing the trajectory of the protagonist, Pip, the study explores how Dickens employs situational, verbal, and structural irony to dismantle Victorian illusions regarding social class, wealth, and the moral standing of a “gentleman.” The research highlights the ironic contrast between the source of Pip’s fortune—the convict Magwitch—and the aristocratic decay of Satis House, suggesting that true nobility resides in moral integrity rather than inherited or acquired status. Furthermore, the paper critiques the systemic biases within the Victorian legal system and the dehumanizing effects of unbridled social ambition. Ultimately, the thesis argues that Dickens’s use of irony serves as a profound moral compass, forcing a reappraisal of human values in a materialistic society.